2010
DOI: 10.1002/nau.20830
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid ameliorates bladder hyperactivity via the inhibition of H2O2‐enhanced purinergic and muscarinic signaling in the rat

Abstract: These results indicate that hyaluronic acid treatment can ameliorate H(2)O(2)-induced bladder hyperactivity possibly via the antioxidant activity and the inhibition of activating purinergic and muscarinic signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…Recent studies in lower urinary tract symptom (LUTS) patients suggest that the obstruction of a bladder urothelial membrane and an increase of oxidative stress followed a bladder ischemia and inflammation may cause urinary dysfunction (37,38). Furthermore, it has been shown that that an intravesical administration of H 2 O 2 evokes immediately detrusor overactivity in anesthetized rats by continuous cystometrography, and oxidative stress induced by H 2 O 2 sensitizes the capsaicinsensitive C-fiber afferent pathway, thereby inducing detrusor overactivity (30,31). The present findings further support the hypothesis that ROS play a key role n the generation of inflammatory and overactive bladder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies in lower urinary tract symptom (LUTS) patients suggest that the obstruction of a bladder urothelial membrane and an increase of oxidative stress followed a bladder ischemia and inflammation may cause urinary dysfunction (37,38). Furthermore, it has been shown that that an intravesical administration of H 2 O 2 evokes immediately detrusor overactivity in anesthetized rats by continuous cystometrography, and oxidative stress induced by H 2 O 2 sensitizes the capsaicinsensitive C-fiber afferent pathway, thereby inducing detrusor overactivity (30,31). The present findings further support the hypothesis that ROS play a key role n the generation of inflammatory and overactive bladder.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, excess ROS generated endogenously can lead to lipid peroxidation, protein oxidization, and DNA damage in the bladder. Recent studies demonstrate that an intravesical injection of H 2 O 2 causes immediately detrusor overactivity in anesthetized rats, suggesting ROS show the stimulatory effect on the bladder afferent fibers directly and/or indirectly (30,31). However, the long-term effects of an intravesical injection of H 2 O 2 on structural and functional changes of the bladder have not been clarified.…”
mentioning
confidence: 99%
“…In cyclophosphamide-induced cystitis in rats, there are substantial changes in both sympathetic and parasympathetic efferent nerves, which affect the afferent nervous input from the bladder; changes in parasympathetic innervation occur prejunctionally, while changes in sympathetic innervation postjunctionally [263]. It has been reported that hyaluronic acid reduced bladder hyperactivity by inhibiting H 2 O 2 -enhanced purinergic and muscarinic signalling [734].…”
Section: Detrusor Overactivitymentioning
confidence: 99%
“…In rat bladder, hyaluronic acid ameliorated H 2 O 2 -induced hyperactivity, possibly via the antioxidant activity and the inhibition of purinergic and muscarinic signaling pathway [83]. In rat vascular smooth muscle cells of the aorta, M 3 receptors were involved in heparin-dependent relaxation [32].…”
Section: Muscarinic Receptor and Extracellular Matrix Moleculesmentioning
confidence: 99%